MATHEMATİCAL APPROACH TO THE ROLE OF INWARD AND OUTWARD FOREIGN DIRECT INVESTORS-LED DIFFUSION OF INNOVATION IN SINO ECONOMIC CONVERGENCE-DIVERGENCE IN LIGHT OF ROGERS’ DIFFUSION OF INNOVATION THEORY AND ECONOMİC CONVERGENCE-DİVERGENCE THEORY - Yurdagul, Esin (WILAYAH: The International Journal of East Asian Studies, 2023)
In 1962, Everett M. Rogers coined and developed his own theory of Rogers’ diffusion of innovation. The last decades have witnessed the fact that innovation has come to be very prominent as a means of economic convergence. Due to the set of the flow data through the amount of Sino inward and outward foreign direct investments remitted by dint of the table between the years of 1980 and 2021, the present research study will analyze the role of inward and outward foreign direct investors-led diffusion of innovation in Sino economic convergence-divergence in light of Rogers’ diffusion of innovation theory and economic convergence-divergence theory in the context of mathematics.